EVALUATION THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN MATHEMATICS LEARNING - Nur Ikhsan Ismail; Baso Intang Sappaile; Iwan Suhardi (Jurnal Eduscience)
Purpose—This research is an evaluative study that aims to evaluate the implementation of the Merdeka curriculum in mathematics learning at SMP Negeri 1 Duampanua.